2016
DOI: 10.18203/2349-3933.ijam20162498
|View full text |Cite
|
Sign up to set email alerts
|

Profile of coronary artery disease cases in diabetics and non-diabetics: a comparative prospective study

Abstract: Background: Diabetes mellitus is one of the commonest disease worldwide ranking next to cardiovascular disorder. The estimated prevalence of diabetes among adults is expected to rise about 100% in future. Cardiac involvement in diabetes commonly manifests as CAD and less commonly as dilated (diabetic) cardiomyopathy and autonomic cardiovascular neuropathy. The risk of CAD among diabetic patients is directly related to the levels of blood pressure, cigarette smoking and total cholesterol. Methods: The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The prevalence of CAD increases as age advances. Most of the studies we reviewed also had similar findings, of average age of occurrence of CAD around 55 years [6][7][8][9][10]. Mean age of our study group was 52.15+6.81 years, which was almost nearer.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The prevalence of CAD increases as age advances. Most of the studies we reviewed also had similar findings, of average age of occurrence of CAD around 55 years [6][7][8][9][10]. Mean age of our study group was 52.15+6.81 years, which was almost nearer.…”
supporting
confidence: 71%
“…were almost similar and few other studies also showed no age difference in the occurrence of CAD among diabetics and non diabetics. [7][8][9][10][11][12][13] When gender ratio was compared between diabetic and non diabetic CAD groups, we found a major difference. In non diabetic CAD study population, male predominance in occurrence of CAD was found, ratio being 4.5:1.…”
Section: Resultsmentioning
confidence: 99%